Present(ed) bodies, absent agency: “patients’ perspectives” at the Museum Vrolik of the body and medicine - Azia Lafleur (Frontiers in Sociology)
Medical exhibits are complex spaces, especially when displaying human remains. This research focuses on Amsterdam’s Museum Vrolik, a prominent museum of the body and medicine in the Netherlands with an important role in the conservation and exhibition of the material heritage of Dutch medicine of the 18th and 19th centuries. I am interested in the affective encounters that are at play in such a setting between us—the living—and the remains on display: How the agency and subject-hood of those who lived and live with ill health, medicalization and disability are effectively present and absent in the context of affective influences in the Museum Vrolik. I deploy the concept of “patients’ perspectives” as a conceptual tool for looking at those who have been impacted by medicine’s medicalizing gaze and handling. Their presence/absence is investigated by using embodied inquiry to attend to the affective encounter between the audience and the bodily remains on display, as felt through the embodied experiencing of visiting the exhibit and mediated by the cultural, physical and institutional context and curation of the Vrolik itself. To analyze the resulting data, I take the museum as a site of storytelling with its curatorial techniques and texts acting as narratological frames and “orientation devices”. The most central pattern emerged as a dissonance between the affective orientation I bring into the space due to my own situated-ness and the orientations prompted by the museum’s frames. The remains on display have been decontextualized from their original home as a part of someone, and transformed into “specimens”. At the same time, my lived experience and identity as a person with chronic illness brought an impulse/intensity towards identification and closeness to the “specimens”, grasping for a sense of their agency, voices, perspectives, personhood. To move forwards from here, persons with disabilities, illness, bodily differences, impairment and injury need to be included and recognized in their capacity as knowers, as having vital embodied knowledge via their lived experience, as narrators and subjects in the stories that are told.